Maximizing the International Human Rights Litigation Toolkit: the Role of Consensus - Francisco Pascual-Vives (Paix et Sécurité Internationales, 2021)
Amongst the instruments making up the strategies for international human rights litigation, the notion of consensus constitutes a tool that is made available to the disputing parties by public international law. When expertly used, consensus can be quite useful to those invoking an evolutive interpretation and wishing to increase the scope of the rights protected by an international human rights treaty, as well as to those wishing to justify the necessity and the proportionality of the restrictions upon a right. This paper offers some recommendations to those practitioners seeking to invoke the notion of consensus in international human rights litigation through a systematisation of the practice before the Europ